Surveillance and evaluation of vector control in Fuyang District, Hangzhou for the 19th Asian Games - XU Jie; PAN Wenjin; TANG Renyu; DU Liqun (Shanghai yufang yixue)
ObjectiveTo assess the risk of vector-born infectious diseases by monitoring the major vectors in the relevant venues of the 19th Hangzhou Asian Games in Fuyang competition area, so as to provide references for the prevention and control of vector in similar large-scale events or activities in the future.MethodsFrom April to October 2023, monitoring and evaluation of rodent, mosquito, fly and cockroach density levels were carried out in various venues and reception hotels in Fuyang competition area (venues and hotels were the 1st circle area, and various environments and places in the surrounding 500 meters were the 2nd circle area). SPSS 25.0 software was used to analyze the data, and chi-square test or Fisher’s precision probability test were used to calculate the qualified rate and positive rate. Moreover, the path index, landing index and Bretrau index were analyzed by Kruskal-Wallis H test.ResultsThe control effect of vector density in the 1st circle was significantly better than that in the 2nd circle. Since September, the monitoring indices of the venues in the two circles had reached the national A-level and B-level standard, respectively. The positive rate of rodent traces generally showed a trend of first increasing and then decreasing, and the peak was shown to occur in July and August, with the highest rate of 5.38%. The qualified rate of rodent prevention facilities continued to rise, and facilities in the 1st and 2nd circles had reached national A-level and B-level standard respectively in late August. The landing index and path index of mosquitoes basically showed a changing trend from high to low, with the highest landing index of 4.56 individuals·person-time-1 and the highest path index of 2.44 places·km-1.The adult fly infestation rate remained at a low level, with the highest rate of 4.17%, and the minimum qualified rate of fly prevention facilities was 28.57%, which reached the national standard after July. The positive detection rates of adult flies and cockroach traces showed no significant pattern, with the highest rate of 7.00% and 8.33%, respectively. The detection rate of live ootheca was always at a low level.ConclusionThe relevant venues in the Fuyang competition area of the 19th Asian Games in Hangzhou meet national standards in terms of vector control indicators such as rodents, mosquitoes, flies, cockroaches and other vectors. By means of environmental improvement, facilities for preventing rodents and flies, and deepening biological and chemical prevention and control methods, it can be ensured that there will be no vector-borne diseases and infestation incidents during the event.